097 Risk management of post-operative anaemia in a multidisciplinary hospital. (23rd September 2015) - Ausset, Sylvain; Schaal, Jean-Vivien; Albin, Vichard; Vincent, Foisseau; Boutonnet, Mathieu; Muller, Violaine; Auroy, Yves
Abstract : Background: Inadequate management of blood losses is one of the leading cause of postoperative morbidity.1 The most commonly involved surgery is orthopaedic surgery and the main issue seems to be delayed transfusion.2 Having validated the relevance and feasibility of a querying method, 3 we studied the variations of indicators extracted from biological databases according to corrective measures aiming to detect and correct postoperative anaemia. Methods: The corrective measures were: (1) The definition and the communication of transfusion thresholds during preoperative evaluation (2) An early telephone warning from laboratory in case of anaemia. The chosen indicator was the incidence of elderly patients sustaining delayed transfusion defined by a haemoglobin (Hb) level beyond transfusion threshold on two consecutive dosages two distinct days. Surgical blood losses before (P1) and after corrective measures (P2) were also compared. Results: The incidences of delayed transfusion in the elderly after orthopaedic surgery the year before and the 3 years following corrective measures were respectively: 22, 16, 9 and 15% (p=0.048) for a transfusion threshold of 9 g/dl Hb and 3.2, 4.4, 1.4, 1.6% for a transfusion threshold of 8 g/dl Hb (ns). There was no difference between P1 and P2. Discussion: A population based follow-up of postoperative haemorrage can be drawn by monitoring electronic databases. This allows an indicator of control of postoperative anaemia. Introduction: La gestion des pertes sanguines est une des principales causes de morbi-mortalité postopératoire.1 La spécialité la plus fréquemment concernée est l'orthopédie et le principal problème en cause semble être le retard transfusionnel2 Après avoir validé la pertinence et la faisabilité d'une méthode d'interrogation, 3 nous avons étudié les variations des indicateurs fournis par les bases de données issues des laboratoires de biologie en fonction des mesures destinées à détecter et traiter l'anémie postopératoire. Matériel et méthodes: Les mesures correctrices étaient: (1) la définition et la communication de seuils transfusionnels dés la consultation d'anesthésie (2) la communication téléphonique précoce des anémies par le laboratoire. L'indicateur choisi était le taux de retards transfusionnels après chirurgie orthopédique chez le vieillard défini par une anémie deux jours consécutifs. Les saignements chirurgicaux avant (P1) et après mesures correctrices (P2) ont également été mesurés. Résultats: Les taux de retard transfusionnel après chirurgie orthopédique chez le vieillard pour l'année précédant les mesures correctrices et les trois suivantes étaient respectivement de: 22, 16, 9 et 15% (p=0, 048) pour un seuil défini à 9 g/dl d'Hb et 3, 2, 4, 4, 1, 4, 1, 6% (ns) pour un seuil défini à 8 g/dl d'Hb. Il n'existait pas de variation statistiquement significative du saignement chirurgical entre P1 et P2. Discussion: Le suivi biologique collectif du saignement postopératoire en orthopédie peut être recueilli « à la sortie de l'automate » et constituer un outil de mesure de l'efficacité de la maitrise du risque d'anémie postopératoire.